1994
DOI: 10.1016/s0022-5223(94)70328-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve operation in patients with the Marfan syndrome

Abstract: Optimal surgical treatment of mitral regurgitation in the Marfan syndrome (valve repair versus replacement) is controversial because the underlying connective tissue defect theoretically might compromise repair durability. To examine the results of mitral valve repair in these patients, we did a retrospective review of 160 patients with the Marfan syndrome who had cardiac surgical procedures between January 1983 and January 1993. Thirty-six patients had mitral procedures, 29 of which were repairs. Mitral valve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…24 Although freedom from reoperation after 15 years after MVR is around 95% for idiopathic MVP, some studies have documented the potential for recurrence of significant MV regurgitation of 1 to 2% of patients per year. 18,25 In our cohort, we had no early mortality that was also previously reported by Gillinov et al and Bhudia et al In these studies, long-term survival after MVR was 83.3% after 10 years in the cohort of Gillinov et al that is comparable with the reported 80% of Bhudia et al and with 78.9% of Fuzzelier et al 5,26,27 No patient of our study needed late MV replacement. Other series also reported good long-term performance of the reconstructed valves with a low risk of late MV replacement with freedom from MV reoperation of 87.1 to 96% at 10 years.…”
Section: Discussionsupporting
confidence: 88%
“…24 Although freedom from reoperation after 15 years after MVR is around 95% for idiopathic MVP, some studies have documented the potential for recurrence of significant MV regurgitation of 1 to 2% of patients per year. 18,25 In our cohort, we had no early mortality that was also previously reported by Gillinov et al and Bhudia et al In these studies, long-term survival after MVR was 83.3% after 10 years in the cohort of Gillinov et al that is comparable with the reported 80% of Bhudia et al and with 78.9% of Fuzzelier et al 5,26,27 No patient of our study needed late MV replacement. Other series also reported good long-term performance of the reconstructed valves with a low risk of late MV replacement with freedom from MV reoperation of 87.1 to 96% at 10 years.…”
Section: Discussionsupporting
confidence: 88%
“…Most existing surgical literature has focused on the management of aortic disease in this patient population. The few reports regarding MV surgery in the MfS population are from major MfS reference centers and have shown that patients with MfS have superior long‐term outcomes when undergoing mitral valve repair (MVr), compared to mitral valve replacement (MVR) . This is congruent with current American and European guidelines stressing MVr over MVR in the management of degenerative mitral valve disease (DMVD) .…”
Section: Introductionsupporting
confidence: 57%
“…These reports, however, are from MfS surgical reference centers and demonstrate a robust MVr rate when compared to the rates in this study. Gillinov et al were able to achieve 81% MVr rate in their MfS population with mitral pathology. Similarly, Helder et al report a 60% MVr rate in their cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Sixty to eighty percent of patients with Marfan's syndrome had mitral valve dysfunction . Mitral valve morphology demonstrated annular dilation, annular calcification, fibromyxomatous changes of leaflets and chordae, chordal rupture and elongation, and leaflet fenestration . Moreover, chronic type A dissection is not uncommon in China due to delayed diagnosis and surgical treatment for patients with acute type A dissection .…”
Section: Discussionmentioning
confidence: 99%